(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Food delivers energy to Human beings; hence it is necessary that energy required for cooking the food is obtained from alternate source of energy, instead of using the conventional energy sources such as wood, Cow-dung, Kerosene, Liquid Petroleum Gas (LPG) and Electricity as well. Solar energy is utilized in solar cooker which makes it eco-friendly and clean. There are various types of solar cookers available in the market, depending on the demand of customer, but still the utilization is not sufficient. Some of the factors are bulky size, heavy weight, working place and required cooking time and the most important is the awareness about using solar cooker. Hence to make solar cooker easy to use and smaller in size with minimum cost is major challenge. Use of parabolic solar cooker has boosted the cooking process. There is certainly scope for research in solar cookers.